Produktivitas Minyak dan Kandungan Asam Lemak Thalassiosira Sp. yang Dikultivasi dengan Makronutrien Pupuk - Rosmaya Dewi (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2017)
: Previous study showed that the diatom Thalassiosira sp. was potential as a source of biodiesel fuel from lipids (oils). To determine biomass productivity as well as oil productivity in large-scale outdoor photobioreactors, the present study investigated the biomass production and optimization of growth macronutriens medium composition from fertilizers. The oils were extracted in chloroform: methanol (1:1) and analyzed by the GC-FID method. The results showed that the best medium composition to grow algal cells contained fertilizers of TSP-36 and Si-P-(PG) with a final concentration of each 10 mg/L with the highest cell density was 3.00 × 106 cells/mL and 4.90 × 106 cells/mL, respectively. The average of biomass productivity as wel as and oil productivity of Thalassiosira sp. cultivated in the outdoor photobioreaktors was 0.08 g/L culture/d and 22.50 µL/L culture/d, respectively.Thalassiosira sp. oil contained fatty acids of 0.30 mg/g capric acid (C10:0), 0.18 mg/g lauric acid (C12:0), 0.23 mg/g palmitic acid (C16:0), 0.50 mg/g stearic acid (C18:0), and 0.52 mg/g oleic acid (C18:1).